Identificação humana por meio do estudo de imagens radiográficas odontológicas: relato de caso - Scoralick, Raquel Agostini [UNESP] (2013)
INTRODUCTION: Among the various documents that make up a dental chart, we value the imaging exams for purposes of human identification, and among them the radiographic, which, when carefully produced and properly archived, allow the identification of any person, in addition to being of low cost. Mainly for these reasons they are fundamental to the process of human dental identification. OBJECTIVE: To describe one case of identifying a burned individual via radiographic analysis of the dental arch and to demonstrate that odontological human identification is effective and low cost. MATERIAL AND METHOD: To identify a burn victim, we proceeded to compare a panoramic dental X-ray made prior to the fatality with the post-mortem periapical radiographs. RESULT: Twelve points of similarity were found between the images studied, which were enough to positively identify the cadaver. CONCLUSION: The study in question allowed us to show that the odontological method of human identification is effective, low cost, and has a good margin of safety, since it works with highly individualized characteristics.